Analisis Kelengkapan Pengisian Berkas Rekam Medis Pasien Rawat Inap RSUP Dr. Kariadi Semarang - Selvia Juwita Swari; Gamasiano Alfiansyah; Rossalina Adi Wijayanti; Rowinda Dwi Kurniawati (Puslitbang Sinergis Asa Professional, 2019)
The completeness of medical record file in December 2018, January 2019 and February 2019 is not complete, so it does not Fulfill the Minimum Standards of Hospital Services. The incomplete filling of medical record files will cause the records to be out of sync and the patient's previous health information difficult to identify. The purpose of the study was to identify the completeness of filling medical record files and the factors causing incompleteness of filling medical record files for inpatients at RSUP Dr. Kariadi Semarang. This research was a qualitative research. The research subjects consisted of 2 officers in charge of medical records. The object of the study was 86 samples of inpatient medical record files from 25-28 February 2019 based on the Slovin formula. The results of the research that the completeness of the patient's identity, the completeness of important reports, the completeness of inpatient medical record file authentication and the completeness of correct recording, indicated that the completeness of filling the medical record was quite high. The incompleteness of filling in the inpatient medical record file was caused by several factors, specifically the officer factor (man), procedural factor (method), tool factor (material), machine factor and motivation factor.